Therapeutic Potential of Cannabidiol (CBD) for Skin Health and Disorders - Baswan SM; Klosner AE; Glynn K; Rajgopal A; Malik K; Yim S; Stern N (Dove Medical Press, 2020)
Sudhir M Baswan,1,* Allison E Klosner,2,* Kelly Glynn,1 Arun Rajgopal,1 Kausar Malik,1 Sunghan Yim,1 Nathan Stern1 1Innovation and Science, Amway Corporation, Ada, MI, 49355, USA; 2Innovation and Science, Nutrilite Health Institute, Amway Corporation, Buena Park, CA, 90621, USA*These authors contributed equally to this workCorrespondence: Sudhir M Baswan Amway Corporation, 7575 Fulton St E, Ada, MI 49355, USATel +1-616-787-0216Email sudhir.baswan@amway.comAbstract: Though there is limited research confirming the purported topical benefits of cannabinoids, it is certain that cutaneous biology is modulated by the human endocannabinoid system (ECS). Receptors from the ECS have been identified in the skin and systemic abuse of synthetic cannabinoids, and their analogs, have also been associated with the manifestation of dermatological disorders, indicating the effects of the ECS on cutaneous biology. In particular, cannabidiol (CBD), a non-psychoactive compound from the cannabis plant, has garnered significant attention in recent years for its anecdotal therapeutic potential for various pathologies, including skin and cosmetic disorders. Though a body of preclinical evidence suggests topical application of CBD may be efficacious for some skin disorders, such as eczema, psoriasis, pruritis, and inflammatory conditions, confirmed clinical efficacy and elucidation of underlying molecular mechanisms have yet to be fully identified. This article provides an update on the advances in CBD research to date and the potential areas of future exploration.Keywords: cannabidiol, CBD, cannabinoids, endocannabinoids, endocannabinoid system, skin, CB1, CB2, FAAH, AEA